Systematic palaeontology and taphonomic significance of the mollusc fauna from the Mata Amarilla Formation (lower Upper Cretaceous), southern Patagonia, Argentina - Griffin, Miguel (2012)
Thirteen mollusc taxa are described from the Mata Amarilla Formation, a lower Upper Cretaceous unit exposed in southern Patagonia, Argentina. Of these, one is a new bivalve species, . Pterotrigonia flava sp. nov. The fauna was collected from two sections representing different parts of the basin. Sedimentary characteristics at each one, together with the fossil content and taphonomic features of the preserved material, confirm that these localities represent littoral environments (lagoon). The two sections contain autochthonous elements, and beds with mixed autochthonous and parautochthonous fauna. The latter exhibits a marine shoreface influence, possibly owing to washover deposits. The possible age of the fossil-bearing rocks in the sections studied is late Albian-early Cenomanian. © 2012 Elsevier Ltd.